Development and implementation of IT products - Lukianchuk, Iurii (Lutsk: LNTU, 2026)
These methodological guidelines are designed for laboratory work in the course "Development and Implementation of IT Products" for first-level (Bachelor's) students in the field of knowledge 12 – Information Technology. The publication covers the complete startup lifecycle, from idea generation and team formation to market analysis, minimum viable product (MVP) development, and investment attraction. The laboratory work is based on modern approaches such as Lean Startup, Customer Development, and Agile, and includes practical tasks on creating empathy maps, formulating hypotheses, calculating TAM/SAM/SOM, and developing a 7Ps marketing strategy. Special attention is paid to developing teamwork skills, analyzing the competitive environment, and communicating with potential investors. The guidelines are intended for full-time and part-time students.
Keywords: startup; IT product; MVP (Minimum Viable Product); customer development; business model; value proposition; market analysis; investors; team building; marketing mix (7Ps).